2022
DOI: 10.3390/bios12100824
|View full text |Cite
|
Sign up to set email alerts
|

A Pervasive Pulmonary Function Estimation System with Six-Minute Walking Test

Abstract: Self-monitoring for spirometry is beneficial to assess the progression of lung disease and the effect of pulmonary rehabilitation. However, home spirometry fails to meet both accuracy and repeatability criteria in a satisfactory manner. The study aimed to propose a pervasive spirometry estimation system with the six-minute walking test (6MWT), where the system with information management, communication protocol, predictive algorithms, and a wrist-worn device, was developed for pulmonary function. A total of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Individuals with COPD often experience a decline in their walking performance, which can have a profound impact on their overall quality of life. The 6-min walking test (6MWT) is commonly used to estimate pulmonary function impairment in individuals with COPD and to assess the extent of the disease [ 8 ]. Researchers have shown that a distance of 350 m in the 6MWT is a threshold for classifying COPD patients at high risk of mortality, hospitalization, and exacerbation of the condition[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with COPD often experience a decline in their walking performance, which can have a profound impact on their overall quality of life. The 6-min walking test (6MWT) is commonly used to estimate pulmonary function impairment in individuals with COPD and to assess the extent of the disease [ 8 ]. Researchers have shown that a distance of 350 m in the 6MWT is a threshold for classifying COPD patients at high risk of mortality, hospitalization, and exacerbation of the condition[ 9 ].…”
Section: Introductionmentioning
confidence: 99%